Strategy of License Services to Increase Investment in Bogor Regency - Hendra Gunawan; Dedi Budiman Hakim; Himawan Hariyoga (Universitas Udayana, 2020)
Abstract License services is a requirement to increase investment in Bogor Regency. As an area close to the national capital, many businessman really take an interest in invesment in Bogor Regency. However, the annualy realization of investments is not in line with the expectations. This fact is really interesting to be studied. This study aimed to analyze the quality of service and satisfaction of the public as users of permit service, analyze the suitability between permit service and laws and regulations, and determine service strategies to increase investment in Bogor Regency. The method used was descriptive analysis with a qualitative approach using Community Satisfaction Survey (SKM) and analytical network process (ANP). The results of this study indicate that the Community Satisfaction Index (IKM) regarding performance and public satisfaction on permit service is not good (2.77). Meanwhile, the results of the analytical network process (ANP) on alternative policies to overcome those problems are the Optimization of SOP Implementation (2.84), Quality Improvement and Quantity of HR (0.277), Budget Additions (0.241), the determination of the Technical Team under One Roof (0.186). Keywords: permit service, increasing investment, community satisfaction survey (SKM),analytical network process (ANP).